2019
DOI: 10.1111/gbb.12624
|View full text |Cite
|
Sign up to set email alerts
|

Sociability development in mice with cell‐specific deletion of the NMDA receptor NR1 subunit gene

Abstract: Social affiliative behavior is an important component of everyday life in many species and is likely to be disrupted in disabling ways in various neurodevelopmental and neuropsychiatric disorders. Therefore, determining the mechanisms involved in these processes is crucial. A link between N-methyl-D-aspartate (NMDA) receptor function and social behaviors has been clearly established. The cell types in which NMDA receptors are critical for social affiliative behavior, however, remain unclear. Here, we use mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 127 publications
(285 reference statements)
0
5
0
Order By: Relevance
“…Previous studies on parvalbumin (Pv)-positive neurons, a major GABAergic neuron type 24 , reported key roles of Pv neurons in the regulation of social cognition and behaviors 21,25,26 . Currently, whether and how the abovementioned ASD-related NMDAR dysfunctions are associated with GABA or Pv neuronal dysfunctions and social deficits have remained largely obscure [27][28][29][30] .…”
mentioning
confidence: 99%
“…Previous studies on parvalbumin (Pv)-positive neurons, a major GABAergic neuron type 24 , reported key roles of Pv neurons in the regulation of social cognition and behaviors 21,25,26 . Currently, whether and how the abovementioned ASD-related NMDAR dysfunctions are associated with GABA or Pv neuronal dysfunctions and social deficits have remained largely obscure [27][28][29][30] .…”
mentioning
confidence: 99%
“…Notably, neonatal testosterone treatment did not affect litter size, pup mortality, or sex distribution (data not shown). Additionally, veh-treated mice exhibited behavior statistically equivalent to that of mice that were undisturbed as neonates (no neonatal injection); both social preference indices at ~PN30 and 24 hr fear memory results at ~PN60 were comparable between mice administered veh and never-injected control mice we have collected over various experiments (54)(55)(56)(57). However, there are several caveats to consider, including possible effects of neonatal injections on maternal care, which could in turn affect pup behavior (44,58).…”
Section: Discussionmentioning
confidence: 74%
“…Our data delineate the maturation of spontaneous synaptic transmission in the NAc shell across early postnatal development, uncovering distinct early maturation signatures between C57BL/6J and BTBR mice, strains that display distinct patterns of NAc-mediated social behavior. These synaptic changes coincide with key developmental changes in social communication, play, affiliative and social approach behavior [154][155][156][157][158] , and abridge a period in which environmental conditions and stress bear a disproportionate impact in shaping future social behavior [159][160][161][162][163] . Accordingly, we revealed a restricted time window for the rescue of social interaction deficits in BTBR mice by rapamycin treatment.…”
Section: Discussionmentioning
confidence: 89%